Serum Nesfatin-1 Levels in Patients With Different Glucose Tolerance Levels - Algul, S.; Ozkan, Y.; Ozcelik, O. (Acad Sciences Czech Republic, Inst Physiology, 2016)
The aim of this study was to compare the levels of nesfatin-1 in healthy subjects with those in prediabetic and diabetic patients who have different glucose tolerance levels. Overall, 100 subjects were divided into 5 groups healthy control (C), impaired fasting glycemia (IFG), impaired glucose tolerance (IGT), metabolic syndrome (MS) and type 2 diabetes mellitus, (Type 2 DM). Glycated hemoglobin (HbA1c) assessed the glycemic control. Homeostasis model assessment of insulin resistance (HOMA-IR) was determined using computer analyses. Nesfatin-1 levels were measured using ELISA method. IFG and IGT (prediabetic groups) from MS and Type 2 DM (diabetic groups) differed significantly in HOMA-IR. The nesfatin-1 levels were lower, although not statistically significant, in IFG (0.937+/-0.03 ng/ml, p=0.07) and IGT (1.039+/-0.06 ng/ml, p=0.5) groups compared to healthy subjects (1.094+/-0.07 ng/ml). However, the nesfatin-1 levels were lower in patients with Type 2 DM (0.867+/-0.02 ng/ml, p=0.007) and MS (0.885+/-0.01 ng/ml, p=0.01) compared to healthy subjects. Nesfatin-1 levels were significantly lower in diabetic patients compared to healthy subjects. This study supports the role of insulin resistance in decreased nesfatin-1 levels in patients with Type 2 DM and MS.
Keywords: Type 2 diabetes mellitus; Impaired glucose regulation; Nesfatin-1; Insulin